2022
DOI: 10.3389/fpls.2022.814401
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Arbuscular Mycorrhizal Fungal Consortia Enhance Yield and Fatty Acids of Medicago sativa: A Two-Year Field Study on Agronomic Traits and Tracing of Fungal Persistence

Abstract: Arbuscular mycorrhizal fungi are promoted as biofertilizers due to potential benefits in crop productivity, and macro- and microelement uptake. However, crop response to arbuscular mycorrhizal fungi (AMF) inoculation is context-dependent, and AMF diversity and field establishment and persistence of inoculants can greatly contribute to variation in outcomes. This study was designed to test the hypotheses that multiple and local AMF inoculants could enhance alfalfa yield and fatty acids (FA) compared to exotic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 135 publications
1
10
0
Order By: Relevance
“…Thus, using two primers (NS31 and LSUGlom1) to amplify the 3′ end of the SSU and the 5′ end of LSU rRNA, together with the ITS region, Pellegrino et al (2012) [ 67 ] traced an isolate of Funneliformis mosseae from an inoculum, using the polymerase chain reaction–terminal restriction fragment length polymorphism (PCR-(T)-RFPL) method. Pellegrino et al [ 45 ] also targeted the SSU, ITS, and LSU regions to resolve both local and exotic F. mosseae and R. irregularis AMF strains.…”
Section: Monitoring Survival and Ecological Consequences Of Amf Inocu...mentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, using two primers (NS31 and LSUGlom1) to amplify the 3′ end of the SSU and the 5′ end of LSU rRNA, together with the ITS region, Pellegrino et al (2012) [ 67 ] traced an isolate of Funneliformis mosseae from an inoculum, using the polymerase chain reaction–terminal restriction fragment length polymorphism (PCR-(T)-RFPL) method. Pellegrino et al [ 45 ] also targeted the SSU, ITS, and LSU regions to resolve both local and exotic F. mosseae and R. irregularis AMF strains.…”
Section: Monitoring Survival and Ecological Consequences Of Amf Inocu...mentioning
confidence: 99%
“…Selecting multiple AMF families having contrasting traits that favor diverse conditions can mitigate these compromises and help improve the chances of success in the field. A mixture of foreign inoculants consisting of F. mosseae and R. irregularis had greater persistence in alfalfa root than the respective single strain and local mixture, while also exerting the greatest impact on plant yield, nitrogen and phosphorus content, and fatty acids [ 45 ]. Merely increasing AMF diversity may not produce additional benefits [ 26 ]; however, the selected AMF should include distant family, which is likely to increase the possibility of finding complementary traits, as shown by Parhar et al [ 115 ], who reported that consortia consisting of distant AMF families conferred greater additive effects than closely related ones.…”
Section: Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations